(untitled) - Wolf, Marvin J. (New York, 1983)
Contents: The Japanese conspiracy, green tea and dirty tricks, MITI, the bike races and the great machine tool debacle,...
Keywords: Chính sách công nghiệp,Industrial policy; Nhật Bản,Japan